Juridical Review of the Role of Expert Witnesses in Trials at the Palangka Raya District Court - Exaudi Gultom, Reyson; Farina, Thea; Yuni Pramita, Claudia (Dinasti Research, 2025)
Expert witnesses play a crucial role in the trial process, particularly in explaining technical matters that may not be understood by judges, prosecutors, or lawyers. In the Palangka Raya District Court, the involvement of expert witnesses is frequently encountered in various types of cases. Therefore, it is important to examine the role of expert witnesses in helping judges achieve substantive justice. This study aims to analyze the role of digital forensic expert witnesses in the trial process at the Palangka Raya District Court, specifically regarding their contribution to the evidence of cases based on technical or scientific expertise to assist judges in understanding technical aspects related to cases involving information and electronic transactions that are being processed. This study uses a Normative Juridical method with a descriptive qualitative approach. The focus of the study is the analysis of the court decisions at the Palangka Raya District Court related to the role of digital forensic expert witnesses in the judicial process based on applicable laws and legal literature. Primary data was obtained from laws, court decisions, and secondary data from legal literature and expert opinions. The results of this study conclude that digital forensic expert witnesses play an important role as tools to understand the technical or scientific aspects of electronic devices, networks, and digital data analysis in the decision-making process for judges at the Palangka Raya District Court. To maintain integrity and competence, judges, prosecutors, and legal advisors are expected to be selective and objective when presenting expert witnesses, considering their competence and independence to achieve substantive justice